URGENCY OF MONOTHEISM EDUCATION IN THE FAMILY ON PANDEMIC PERIOD COVID 19 - Hadis Purba (Jurnal Sabilarrasyad, 2020)
The COVID 19 epidemic has engulfed this nation and the world throughout 2020, as a mu'min, then it is better to do quarantine or "social distancing" endeavors, so also improve our spirituality. If you can meditate further, as a Muslim all this plague is a blessing, a stop for those who think, to continue to make it as a wash or a way to continue to draw closer to Allah, so that when the level of surrender is high there will be calm and with all efforts and prayer of salvation also to Allah SWT, by always involving HIM, and hoping that all this plague will end, and can also be immediately found the cause. This understanding of cultivation starts from education in the family. Education in the family must be wrapped with good monotheism education. Monotheism education in the family is monotheism education efforts carried out by parents towards their children by delivering material monotheism with the method of sentence monotheism, exemplary, habituation, advice, and supervision. By teaching monotheism which originates from the Qur'an and Al-Hadith, the monotheism that forms in the soul of a child is accompanied by knowledge based on correct arguments and evidence, and can be justified.